Treatment of Focal-Onset Seizures in Children: Should This Be More Etiology-Driven? - Aeby, Alec; Ceulemans, Berten; Lagae, Lieven (Frontiers in Neurology, 2022)
To accelerate the process of licensing antiseizure medication (ASM) in children, extrapolation of efficacy data for focal-onset seizures from adults to children ≥2 or ≥4 years of age is now accepted. We summarized the efficacy evidence from randomized, controlled trials that was used to grant approval for the pediatric indication of focal-onset seizures for the different ASMs available in Europe. Data from high-quality randomized, controlled trials in young children are limited, especially on the use of ASMs in monotherapy. Licensure trials are typically focused on seizure type irrespective of etiology or epilepsy syndrome. We elaborate on the importance of etiology- or syndrome-driven research and treatment, illustrating this with examples of childhood epilepsy syndromes characterized by predominantly focal-onset seizures. Some of these syndromes respond well to standard ASMs used for focal-onset seizures, but others would benefit from a more etiology- or syndrome-driven approach. Advances in molecular genetics and neuroimaging have made it possible to reveal the underlying cause of a child’s epilepsy and tailor research and treatment. More high-quality randomized, controlled trials based on etiology or syndrome type are needed, including those assessing effects on cognition and behavior. In addition, study designs such as ‘N-of-1 trials’ could elucidate possible new treatment options in rare epilepsies. Broadening incentives currently in place to stimulate the development and marketing of drugs for rare diseases (applicable to some epilepsy syndromes) to more common pediatric epilepsy types and syndromes might be a means to enable high-quality trials, and ultimately allow more evidence-based treatment in children.